2017
DOI: 10.1002/hep.29127
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase Suv39h2 contributes to nonalcoholic steatohepatitis in mice

Abstract: Suv39h2 plays a pivotal role in the regulation of inflammatory response in hepatocytes and macrophages, contributing to NASH pathogenesis. (Hepatology 2017;65:1904-1919).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Previously we have shown that SIRT1 expression is epigenetically regulated in different disease settings. For instance, nutritional stress-induced down-regulation of SIRT1 in both hepatocytes and macrophages appears to be mediated by the histone trimethyltransferase Suv39h2 (42). Similarly, SIRT1 transrepression in cardiomyocytes in response to ischemic stress relies on the histone trimethyltransferase Suv39h1 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that SIRT1 expression is epigenetically regulated in different disease settings. For instance, nutritional stress-induced down-regulation of SIRT1 in both hepatocytes and macrophages appears to be mediated by the histone trimethyltransferase Suv39h2 (42). Similarly, SIRT1 transrepression in cardiomyocytes in response to ischemic stress relies on the histone trimethyltransferase Suv39h1 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Primary mouse hepatocytes were isolated and maintained as previously described by Fan et al (15). The Wnt3a-producing (CRL2647; American Type Culture Collection, Manassas, VA, USA) were maintained as previously described by Soeda et al (16).…”
Section: Cell Culture and Transient Transfectionmentioning
confidence: 99%
“…Increasing evidence has confirmed that dysregulation of SUV39H2 contributes to carcinogenesis and is involved in invasion and metastasis of malignancy [33,36,38,41,42,44]. Recently, researches have also clarified that Suv39h2 knockout decrease the incidence of nonalcoholic steatohepatitis and myocardial infarction [48][49][50]. In this review, we focus on the prognostic value of SUV39H2 in cancers, describe the off-target effects of SUV39H2 on non-histone proteins in epigenetic modification, discuss its potential mechanisms in tumorigenesis and immunotherapy, and, summarize SUV39H2 inhibition as a potential target for anti-cancer therapies ( Table 1).…”
Section: Breast Cancermentioning
confidence: 98%
“…The mRNA and protein expression levels of SUV39H2, G9a and EZH2 are up-regulated in hepatocellular carcinoma (HCC) tissues and SUV39H2 is highly associated with the HCV infection and tumor stage [43]. In hepatocytes, Suv39H2 increases the incidence of nonalcoholic steatohepatitis and steatosis likely via increasing H3K9me3 on Sirt1 gene promoter and promoting SIRT1 trans-repression in mice [48,50]. These all imply a potential role of SUV39H2 in HCC pathogenesis and progression.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%